The Polarization of the Hamas Movement in Palestine and Its Influence on Indonesian Defense Issues: A Geopolitical and Military Overview - Budiman, Ahmad; Hannase, Mulawarman (Journal Of Middle East and Islamic Studies, 2021)
The Israeli-Palestinian conflict has implications for the birth of armed groups that continue to be polarized within Palestine, such as the PLO, Hamas, Fatah, and others to the PNA. However, one group that exists and has a strong resonance in the Islamic world is Hamas. The resonance also reached Indonesia. This study will examine the polarization of Hamas and its military activities which are considered to represent the interests of Palestinian Muslims. As a result, this has a snowball effect by generating bigger and stronger support which ultimately affects the issue of Indonesia's national defense., This study uses a qualitative method with an analysis of geopolitical theory. The results showed that the polarization that occurred was caused by the ideological differences between Hamas and Fatah and the different points of view between Hamas members. Hamas activities in Palestine have no effect on the issue of Indonesian defense because the forms of response are limited to humanitarian solidarity and equality of belief.